Oral complications to head and neck cancer - Bergh, Kristin (Universitetet i Tromsø, 2011)
Patients with head and neck cancer may experience a broad spectre of debilitating oral complications the after radiotherapy and chemotherapy. The aim of this master thesis was to create information pamphlets in order to inform the patients with head and neck cancer about the possible complications of the cancer treatment and measurers to maintain or establish a good oral hygiene. Material and methods was divided in to two parts. Part one was a collection of relevant literature, with Pub Med search and using the text books in my dental curriculum. In addition several information pamphlets used at different hospitals and institutions was collected. Part two was the creation of information pamphlets trying by using the most updated and evidence based measures. During the work with the pamphlet I was introduced to the health literacy term. According to studies one third of the adult population had problems understanding written health information. As a result the pamphlet was created in plain Norwegian language and the most important information was written first. The pamphlet will be distributed to the patients by the hospital dentist at the special clinic in Tromsø (TkNN). The collaboration between the dental teams and the general health services is in an early phase in Tromsø. Hopefully the multidisciplinary collaboration will be further developed since this is beneficial to the especially vulnerable patients, such as patients with head and neck cancer.